2012
DOI: 10.1097/iae.0b013e31821e2057
|View full text |Cite
|
Sign up to set email alerts
|

Role of Topical Nepafenac in Prevention and Treatment of Macular Edema After Vitreoretinal Surgery

Abstract: Topical nepafenac was safe and reduced postoperative pain and inflammation in patients undergoing vitreoretinal surgery. However, its effect on reducing postoperative macular edema and improving visual acuity as compared with that of the standard postvitrectomy therapeutic regimen was equivocal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 16 publications
3
21
0
2
Order By: Relevance
“…After thirty days there was no difference noted in relation to the above-mentioned parameters of inflammation in both groups. In another study by Naithani et al .,[15] patients given nepafenac had significantly less intraocular inflammation on day one, postoperatively, as compared to those who received placebo drops. However, in this study the drops were started three days preoperatively in both the groups and were given in addition to topical prednisolone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After thirty days there was no difference noted in relation to the above-mentioned parameters of inflammation in both groups. In another study by Naithani et al .,[15] patients given nepafenac had significantly less intraocular inflammation on day one, postoperatively, as compared to those who received placebo drops. However, in this study the drops were started three days preoperatively in both the groups and were given in addition to topical prednisolone.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no statistically significant difference in the pain scores between both the groups. Naithani et al .,[15] found that individuals put on nepafenac were statistically significantly less likely to have postoperative eye pain than those in the placebo group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2011), pain and inflammation after vitreoretinal surgery (Naithani et al. 2012), acute central chorioretinopathy (Alkin et al. 2013), postoperative inflammation after small‐gauge vitrectomy (Nagpal et al.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective, randomized, placebo-controlled trial reported that topical ketorolac 0.4% reduced both retinal thickness (9%) and total macular volume (6%) but neither outcome reached statistical significance [29]. Schoenberger et al reported that topical nepafenac more rapidly reduced macular volume in patients undergoing epiretinal membrane surgery, but this effect was not observed by another study using nepafenac [30, 31]. …”
Section: Postoperative Cystoid Macular Edemamentioning
confidence: 99%